AN IMPACT OF RADIOTHERAPY ON PSYCHО-EMOTIONAL CHARACTERISTICS OF CANCER PATIENTS - Volarevic, Ana; Kastratovic, Nikolina; Milosavljevic, Neda; Pavlovic, Dragica; Volarevic, Vladislav (Acta medicae Medianae, 2026)
The psychological distress that cancer patients endure can greatly affect their treatment experience and quality of life, making it crucial to understand the psycho-emotional effects of radiotherapy, an established cornerstone in cancer treatment, as this knowledge is vital for creating comprehensive care strategies that address both physical and mental health needs. The study investigated the psycho-emotional effects of radiotherapy in cancer patients with a focus on the interplay of radiotherapy with hormone therapy, biological therapy, and chemotherapy. Our results indicate that while psychological distress is prevalent among patients undergoing radiotherapy, changes in emotional competence, stress reactions, depression, and mature religiosity are similar to those experienced by healthy individuals. Notably, patients receiving radiotherapy exhibited significantly lower scores on the Interpersonal Reactivity Index (IRI), altruism, and the Beck Anxiety Inventory (BAI) compared to healthy controls, suggesting that, while anxiety and empathy fatigue did not increase, reduced altruism could reflect a preoccupation with personal health challenges. A higher externality score among radiotherapy patients indicates a search for external justifications for their illness. The introduction of hormone therapy significantly increased religiosity scores, enhancing emotional acceptance of illness, while biological therapy resulted in diminished religiosity, likely due to its unfamiliarity and associated skepticism. Importantly, chemotherapy did not significantly alter radiotherapy-induced psycho-emotional effects, reinforcing the notion that familiarity with treatment modalities can foster emotional resilience and a sense of control in patients. In conclusion, this study underscores the importance of addressing psycho-emotional well-being in comprehensive cancer care of radiotherapy-treated patients.
Keywords: radiotherapy, psycho-emotional characteristics, altruism, emotional competence, stress